Imitasi Dalam Komunikasi Matematis Siswa Untuk Menyelesaikan Masalah Matematika - Andika Setyo Budi Lestari; Toto Nusantara; Susiswo Susiswo; Tjang Daniel Chandra (Universitas Sarjanawiyata Tamansiswa, 2019)
Imitation-related studies have been widely studied in children with autism, infants and young children. Imitation in the learning process is inseparable. The study of imitation in adults and school-aged children is still rarely studied, so the researcher was interested in conducting imitation-related research in mathematical communication in junior high school learners of class VII in one of the public schools in Bangil, Pasuruan, Indonesia. The type of the research was a qualitative research. The main instrument in this study was the researcher herself. The data sources in research were in the form of learner works, interview recordings, and field notes. The results showed that junior high school learners of class VII who became the subject of this research in communicating the completion of mathematical problems in doing an imitation towards elementary school teachers (primary school).The finding in this study was that personal closeness truly affects the imitations made by students in solving mathematical problems.